Nutrient compositional variation and interrelationship in the muscle of wild and plastic-reared brachyuran - Moruf, Rasheed Olatunji (Acta Scientiarum. Animal Sciences, 2022)
Edible brachyurans are recognized as a popular source of food due to their delicious taste and nutritional quality. This study investigated the nutrient compositional variation and interrelationship in the muscle of wild and plastic-reared Cardisoma armatum. The plastic-reared crab had 27.81 ± 2.29 g 100 g-1 protein while crab from the wild contained 22.45 ± 2.65 g 100 g-1 protein. The difference in protein content of plastic-reared and its counterpart from the mangrove swamp was not significantly different (p > 0.05). This is also true of other proximate composition except that wild crabs were slightly higher in both crude fat (2.68 ± 0.35 g 100 g-1) and carbohydrate (5.89 ± 3.05 g 100 g-1). Generally, the total energy contributed due to protein, carbohydrate and fat in the tissues of both wild and plastic-reared C. armatum are similar. In the wild crab, contents of calcium (16083.27 ± 2127.90 mg 100 g-1) and phosphorus (1191.42 ± 199.21) were relatively higher, while contents of magnesium (368.69 ± 111.05 mg 100 g-1), sodium (125.30 ± 11.18 mg 100 g-1) and potassium (87.36 ± 7.27 mg 100 g-1) were relatively higher in plastic-reared crabs. All significant mineral ratios in wild and plastic-reared C. amartum fall within acceptable range. The positive relationship in the nutritional quality indicates that changes in proximate composition are associated with changes in mineral contents of the crab tissue.